2010
DOI: 10.1136/tc.2009.033217
|View full text |Cite
|
Sign up to set email alerts
|

Divergence between strength indicators in packaging and cigarette engineering: a case study of Marlboro varieties in Australia and the USA

Abstract: Colour can be used to market cigarettes as 'milder', independently of ISO yields and 'Light'/'Mild' descriptors. Banning of 'Light' and 'Mild' brand descriptors may be inadequate to end belief in less harmful cigarettes so long as the tobacco industry remains free to engineer 'mildness' and to use colours, other descriptors and design features to characterise varieties it wants to market as 'milder'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…For example, package testing on Camel filter cigarettes showed that increasing the amount of white space on the pack and lightening brown colours reduced the smokers’ perception of the cigarette strength 14. Such subterfuge packaging strategies could instil consumer perceptions that are inconsistent with the actual emission yields 20. These findings call for stronger measures to regulate tobacco packaging.…”
Section: Discussionmentioning
confidence: 99%
“…For example, package testing on Camel filter cigarettes showed that increasing the amount of white space on the pack and lightening brown colours reduced the smokers’ perception of the cigarette strength 14. Such subterfuge packaging strategies could instil consumer perceptions that are inconsistent with the actual emission yields 20. These findings call for stronger measures to regulate tobacco packaging.…”
Section: Discussionmentioning
confidence: 99%
“…While perceptions of harmfulness can be manipulated by elements of pack design, seemingly independent of yields(12), it is not just packaging design that affects smokers’ perceptions. The tobacco manufacturers in the UK achieved the lower tar limit set by the 10-1-10 policy by increasing the percentage of filter ventilation in cigarettes, meaning that total intakes of nicotine remained similar.…”
Section: Discussionmentioning
confidence: 99%
“…48 In order to circumvent the regulation, tobacco companies replaced the banned terms with similarly deceptive words (eg, ‘smooth’) or numbers, manipulated the thickness of packaging to indicate that soft packs contained lighter/milder cigarettes than hard packs, 48 and used lighter pack colours to signify lower strength. 50 In many countries including the USA, tobacco companies substituted blue packaging for ‘mild’, gold for ‘light’ and silver for ‘ultralight’ brands. 5051 It is evident that consumers accept colour variation and other cues as indicators of reduced risk 4951 and that further regulation is needed to eliminate the misconception that some cigarettes are less harmful than others.…”
Section: Packagingmentioning
confidence: 99%
“…50 In many countries including the USA, tobacco companies substituted blue packaging for ‘mild’, gold for ‘light’ and silver for ‘ultralight’ brands. 5051 It is evident that consumers accept colour variation and other cues as indicators of reduced risk 4951 and that further regulation is needed to eliminate the misconception that some cigarettes are less harmful than others.…”
Section: Packagingmentioning
confidence: 99%